The comparison of USG measured cervical length in pregnant women with previous induced abortion versus those who have not had an induced abortion - Naidu, Harshita; Hegde, Nivedita; M., Anjali; Kanniga, Rohini; Vasudeva, Akhila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The majority of women who undergo induced abortion are young and of low parity. Hence, it is desirable to look for any association effects of induced abortion with future reproductive outcomes. In this study, we aim to compare ultrasound measured cervical length in pregnant women with previous induced abortion versus those who have not had an induced abortion. Methods: This was a prospective observational study performed at tertiary care hospital. Total of 400 patients were recruited, divided into two groups. Patients with an induced abortion in previous pregnancy were included as cases and those with no history were taken as controls. Cervical length was measured by transvaginal ultrasound in all participants at 11-14, 18-22 and 28-32 weeks. Pregnancies were followed up to note incidence of spontaneous preterm delivery, preterm pre labour rupture of membranes (PPROM), threatened preterm, and second trimester miscarriage. Results: Authors have found that there was no significant difference in the cervical length of pregnant patients with or without a history of prior induced abortions. In our study authors found that mean cervical length at 11-14weeks, 18-22 weeks, and 28-32 weeks was 3.47±0.126cm and 3.48±0.195cm; 3.44±0.296cm and 3.49±0.182cm; 3.36±0.477cm and 3.42±0.310cm respectively among cases and controls. However, there was a demonstrably increased risk of spontaneous preterm delivery, PPROM and threatened preterm in patients with a history of prior induced abortion. Conclusions: Authors conclude that previous induced abortion increases the risk of threatened preterm, PPROM, spontaneous preterm delivery in the subsequent pregnancy. But, this risk is not predictable by measuring cervical length as the mean cervical length remained the same in both the groups.